Real time traceability system for halal transportation - Mohamad, Maizatul Akma; Mansor, Shattri; Ahmad, Noordin; Wan Adnan, Wan Azizun (Halal Products Research Institute, Universiti Putra Malaysia, 2014)
The increasing awareness on the reliability of Halal supply chain that include the logistic process leads to the initiative to obtain standard verification on operations procedure in accordance with Halal standard requirement. The chance of breakage, contamination and pilferage in supply chain of the goods during transportation process is higher due to lack of information sharing and other party not practicing Halal supply chain. Thus, this will lead to the risk of Halal become non-compliant to Halal requirement. Conventionally, the control of Halal logistic industries were done manually with no real time track and trace system that unable to verify doubtful event during the transportation process. The proposed system uses Global Positioning System (GPS) to track the movement of Halal transportation. Geo fences of Halal operators are created to give alert on event occur during transportation process. This geo fences monitoring technique enables the operator to identify the location where the goods are dropped and therefore give information whether the goods have been dropped at the right designated area. A detailed trace of vehicle movement with highlight of the potential chain break is expected to be reported in the forms of map and tabular report. Overall, the proposed system will facilitate JAKIM to take proactive action on suspicious event occur during transportation process.